REMAJA ANTI HOAKS KESEHATAN: EDUKASI FAKTA VS MITOS OBAT DAN HERBAL UNTUK MENINGKATKAN LITERASI KESEHATAN DIGITAL - Abdullah, Dessy; Rinita Amelia (Yayasan Nusantara Hasana Berdikari, 2025)
In the digital era, health hoaxes pose a serious challenge to society, especially adolescents. Misinformation about medicines and herbal products can lead to incorrect health decisions. This community service activity aims to improve adolescent health literacy through myth- and fact-based education related to medicines and herbs. The activities included interactive seminars, group discussions, and educational quizzes. The results showed an increase in participants' understanding of distinguishing between valid and invalid information. This effort is expected to shape adolescents into agents of change in combating health hoaxes in their communities.